2022
DOI: 10.1021/acs.est.2c05579
|View full text |Cite
|
Sign up to set email alerts
|

Shoreline Drying of Microseira (Lyngbya) wollei Biomass Can Lead to the Release and Formation of Toxic Saxitoxin Analogues to the Water Column

Abstract: The harmful, filamentous cyanobacteria Microseira (Lyngbya) wollei produces several toxic analogues of saxitoxin (Lyngbya wollei toxins 1–6, or LWTs 1–6), grows in shallow water, and can deposit significant biomass on nearby shorelines. Here, we show that the LWTs are stable in the biomass during subsequent drying but that the process facilitates the later release of LWTs upon return to the water column. Under basic conditions, LWTs hydrolyzed to generate products that were significantly more neurotoxic than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…For example, Metz et al reported that shoreline drying of Microseira (Lyngbya) wollei biomass can lead to the release and formation of toxic Lyngbya wollei toxins (LWTs) to the water column. 220 These toxins are low molecular weight, are structurally similar to saxitoxins, and have 6 congeners that have been reported in the environment. These LWTs were found to be stable in the dried biomass on the shore but could later release into waters when they rise again.…”
Section: ■ Algal Toxinsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Metz et al reported that shoreline drying of Microseira (Lyngbya) wollei biomass can lead to the release and formation of toxic Lyngbya wollei toxins (LWTs) to the water column. 220 These toxins are low molecular weight, are structurally similar to saxitoxins, and have 6 congeners that have been reported in the environment. These LWTs were found to be stable in the dried biomass on the shore but could later release into waters when they rise again.…”
Section: ■ Algal Toxinsmentioning
confidence: 99%
“…Several interesting fate and transport studies of algal toxins were published. For example, Metz et al reported that shoreline drying of Microseira (Lyngbya) wollei biomass can lead to the release and formation of toxic Lyngbya wollei toxins (LWTs) to the water column . These toxins are low molecular weight, are structurally similar to saxitoxins, and have 6 congeners that have been reported in the environment.…”
Section: Algal Toxinsmentioning
confidence: 99%
“…By 2019, more than 200 distinct benthic mats of M. wollei covered up to 60% of the total shoreline with ~5 × 10 6 kg of biomass that exceeded 10 kg m −2 in some areas [230,231]. Mats that drift into the shore and dry along the shorelines can release potent toxins into the adjacent water column [232]. For this harmful alga, legacy sediment P is much more important than water-column nutrient supplies; in fact, legacy sediment P was the only factor that realistically predicted its observed massive growth [231].…”
Section: Reservoir Water Qualitymentioning
confidence: 99%
“…This cyanobacterium was renamed because of the establishment of a new phylogenetically distinct genus, Microseira from Lyngbya (Kenins 2017). The biphasic filamentous cyanobacterium, M. wollei, is common worldwide and occurs in a diverse array of aquatic systems (e.g., rivers, lakes, springs) in both freshwater and brackish conditions (Metz et al 2022.). This cyanobacterium has previously been named Plectonema wollei, Lyngbya wollei, and Microseiria wollei (Hudon et al 2014;Metz et al 2022).…”
Section: Purposementioning
confidence: 99%
“…The biphasic filamentous cyanobacterium, M. wollei, is common worldwide and occurs in a diverse array of aquatic systems (e.g., rivers, lakes, springs) in both freshwater and brackish conditions (Metz et al 2022.). This cyanobacterium has previously been named Plectonema wollei, Lyngbya wollei, and Microseiria wollei (Hudon et al 2014;Metz et al 2022). M. wollei is historically known within the southeastern US, but its occurrence is becoming increasingly widespread across the eastern US and southern Canada (Putman et al 2022).…”
Section: Purposementioning
confidence: 99%